Evaluation of Timing and Rates for Nitrogen Application for Optimizing Maize Growth and Development and Maximizing Yield. (1st March 2018) - Hammad, Hafiz Mohkum; Abbas, Farhat; Ahmad, Ashfaq; Farhad, Wajid; Wilkerson, Carol Jo; Hoogenboom, Gerrit
Abstract : Core Ideas: Nitrogen fertilizer application increased photosynthesic rates during vegetative development Higher nitrogen fertilizer application rates are not a sound strategy to obtain maximum grain yield Optimum timing of nitrogen applications is essential for maximizing yield Accurately applying N fertilizer is challenging for maize ( Zea mays L.) farmers in semiarid regions. The goal of this study was, therefore, to identify the best rates and timing of N applications for optimum maize development and maximum grain yield (GY). A 2‐yr study (2009 to 2010) was conducted in the semiarid conditions of Faisalabad, Pakistan. Five N application rates were administered at three different times during each growing season. Photosynthesis, GY, N uptake, and N recovery efficiency (NRE) were significantly affected ( P < 0.05) by the rate and timing of N applications. Photosynthesis, GY, and NRE increased linearly following application of 1/3 N at V2, 1/3 N at V16, and 1/3 N at R1 stages (treatment T2 ) with 250 kg N ha −1 . In contrast, the maximum N uptake was observed with an application of 300 kg N ha −1 without a significant increase in GY. The results suggest that N fertilizer recommendations should not be solely based on plant N uptake but also take into account the physiological processes of maize and NRE. Since the optimal N application rate for maximum GY was 250 kg N ha −1, applied in three applications (1/3 N at V2, 1/3 N at V16, and 1/3 N at R1 stages), this rate and timing should be considered as the best fertilizer management practice for semiarid conditions.